(untitled) (Contemporary Journal of Social Science Review, 2026)
This study examined the paradox of ambidextrous leadership by investigating the mediating role of psychological uncertainty in the relationship between leadership style and job satisfaction. A quantitative research design was employed, and data was collected from a sample of 300 employees working in diverse organizational sectors. The analysis used descriptive statistics and structural modeling techniques to evaluate the relationships among variables. The results indicated that ambidextrous leadership demonstrated a high mean value (M = 4.08, SD = 0.69), reflecting strong presence of dual leadership behaviors. Psychological uncertainty showed a moderate mean (M = 3.72, SD = 0.74), indicating noticeable levels of ambiguity in the workplace. Job satisfaction recorded a high mean score (M = 3.95, SD = 0.68), suggesting generally positive employee attitudes. The findings confirmed that ambidextrous leadership positively influenced job satisfaction, while psychological uncertainty exerted a negative effect. Mediation analysis revealed that psychological uncertainty partially mediated the relationship between ambidextrous leadership and job satisfaction, highlighting the dual impact of leadership practices. The study concluded that effective management of uncertainty remained essential for maximizing the benefits of ambidextrous leadership. The findings provided theoretical and practical insights for organizations seeking to enhance employee satisfaction in dynamic environments.